Determination of hemoglobin Bart's in alpha thalassemia traits by two-site immunoradiometric assay. II. Detection of hemoglobin Bart's in alpha thalassemia traits - Makonkawkeyoon L. (2014)
A sensitive method for the determination of minute amounts of Hb Bart's in hemolysate of alpha thalassemia-1 and alpha thalassemia-2 was carried out by two-site immunoradiometric assay. This technique is very sensitive and is able to detect minute amounts of substances. When this method is used with specific anti-Hb Bart's derived from affinity column chromatography, then labelled with radioactive 125I, the two-site immunoradiometric assay will contain both the sensitivity and specificity for the determination of Hb Bart's. In this study, parents of fetus with Hb Bart's hydrops fetalis contained high levels of Hb Bart's 0.73-1.11 per cent (mean +/- S.D. = 0.86 +/- 0.12%). Parents of Hb H diseases had Hb Bart's in two groups. The first group contained high levels of Hb Bart's of 0.73-1.20 per cent (mean +/- S.D. = 0.88 +/- 0.14%), while the second group had levels of 0.39-0.45 per cent (mean +/- S.D. = 0.42 +/- 0.02%). Mothers of patients with Hb H disease contained Hb Bart's of 0.42 +/- 0.48 per cent (mean +/- S.D. = 0.45 +/- 0.02%). Eight out of ten normal subjects contained low levels of Hb Bart's of 0.17-0.26 per cent (mean +/- S.D. = 0.22 +/- 0.04%), while two contained high levels of Hb Bart's of 0.46 and 0.43 per cent respectively. The two-site immunoradiometric assay was able to differentiate the level of Hb Bart's among alpha thalassemia-1, alpha thalassemia-2 and normal subjects.